2019
DOI: 10.1186/s11671-019-3114-8
|View full text |Cite
|
Sign up to set email alerts
|

Scaled-Down c-Si and c-SiGe Wagon-Wheels for the Visualization of the Anisotropy and Selectivity of Wet-Chemical Etchants

Abstract: Wet etching offers an advantage as a soft, damage-less method to remove sacrificial material with close to nanometer precision which has become critical for the fabrication of nanoscale structures. In order to develop such wet etching solutions, screening of etchant properties like selectivity and (an)isotropy has become vital. Since these etchants typically have low etch rates, sensitive test structures are required to evaluate their etching behavior. Therefore, scaled-down single-crystalline Si (c-Si) and Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It has been reported that the Si{100} often exhibits a faster etching rate in practice, especially in the presence of isopropyl alcohol. , However, the calculated result of the etching rate aligns with the vast majority of the literature. With the wagon wheel etch, , laser reflectometry, and depth profiling tests over hemispheric Si, the trend of R {210} > R {110} ≈ R {211} > R {100} > R {111} within the range from room temperature to 90 °C and from 5 to 50 wt % TMAH is consistently reported (where R { hkl } represents the etching rate of the { hkl } plane).…”
mentioning
confidence: 92%
“…It has been reported that the Si{100} often exhibits a faster etching rate in practice, especially in the presence of isopropyl alcohol. , However, the calculated result of the etching rate aligns with the vast majority of the literature. With the wagon wheel etch, , laser reflectometry, and depth profiling tests over hemispheric Si, the trend of R {210} > R {110} ≈ R {211} > R {100} > R {111} within the range from room temperature to 90 °C and from 5 to 50 wt % TMAH is consistently reported (where R { hkl } represents the etching rate of the { hkl } plane).…”
mentioning
confidence: 92%